Variant allele of HSD3B1 increases progression to castration‐resistant prostate cancer. Issue 7 (1st March 2015) - Wu, Gang; Huang, Shengsong; Nastiuk, Kent L.; Li, Jinliang; Gu, Jun; Wu, Ming; Zhang, Qimin; Lin, Hanqing; Wu, Denglong
<x xml:space="preserve">Abstract</x> BACKGROUND 3β‐hydroxysteroid dehydrogenase type 1 (3βHSD1), which is a rate‐limiting enzyme that catalyzes the conversion of adrenal‐derived steroid dehydroepiandrosterone to dihydrotestosterone (DHT), may be a promising target for treating castration‐resistant prostate cancer (CRPC). METHODS From 2004 to 2011, a total of 103 consecutive patients presenting with advanced prostate cancer were included in this study. All patients were treated with surgical castration as androgen‐deprivation therapy (ADT). Germline DNA was extracted from archived tissue from each patient and sequenced. PSA half‐time (representing rate to PSA nadir after ADT), the incidence of, and time to CRPC occurrence, and cause‐specific mortality rates were determined during the 3–10 years follow‐up. The perioperative data and postoperative outcomes are compared. The patients were retrospectively analyzed for survival time. RESULTS Of the 103 patient samples analyzed, 18 harbored a heterozygous variant (1245C) HSD3B1 gene, while 85 patients were homozygous wild‐type (1245A) for HSD3B1. The two groups were homogenous for age, PSA, Gleason and metastases rate preoperatively. The incidence of CRPC observed in the variant group was significantly higher than that of wild‐type group (100% vs. 64.7%, respectively; P = 0.003). Despite this higher incidence of CRPC, there were no significant differences in time to develop CRPC, or in cause‐specific mortality. Further, neither PSA half‐time, nor time to biochemical recurrence were different between the variant and wild‐type groups. CONCLUSION Prostate cancer patients who harbored the heterozygous variant HSD3B1 (1245C) are more likely to develop to CRPC, but do not have shorter time to biochemical recurrence, shorter survival time or higher mortality risk. Prostate 75:777–782, 2015. © 2015 Wiley Periodicals, Inc.